INFLAMMATION AS A THERAPEUTIC TARGET IN THE COMPLEX TREATMENT OF MALIGNANT TUMORS - O. E. Savelieva; V. M. Perelmuter; L. A. Tashireva; E. V. Denisov; A. V. Isaeva (Сибирский онкологический журнал, 2017)
In this review, we analyzed the role of inflammation in carcinogenesis, tumor development, and metastasis. In addition, the mechanisms of non-steroidal anti-inflammatory drugs (NSAIDs) and the reasons of their contradictory influence on cancers were discussed. We summarized the numerous data about effectiveness of anti-inflammatory drugs for the prevention and additional therapy of tumor diseases. In particular, divergent effects of NSAIDs may be due to the peculiarities of immune-inflammatory responses that are realized in carcinogenesis and tumor development that have yet to be studied. We also discussed the selectivity of NSAID effects on different cancers and opposite effects of anticancer drugs with similar mechanisms of action. Apparently, the unsuccessful use of NSAIDs in cancer prevention and therapy are more specific for squamous cell carcinomas. Based on the literature, we provided significant clinical findings regarding the need of NSAID use in the current therapy of certain cancers and the determination of molecular predictors of the drug effect. In fact, anti-inflammatory therapy could eliminate the factors that contribute to the appearance of invasive and metastatic tumor cells, cancer and premetastatic niches and thus prevent metastasis and recurrence. At present, some non-selective (aspirin) and selective (celecoxib) NSAIDs are highly promising in the therapy of solid tumors.